Unearthing how, why, for whom and under what health system conditions the antiretroviral treatment adherence club intervention in South Africa works: A realist theory refining approach - Ferdinand C. Mukumbang; Bruno Marchal; Sara Van Belle; Brian van Wyk (BMC, 2018)
Abstract Background Poor retention in care and suboptimal adherence to antiretroviral treatment (ART) undermine its successful rollout in South Africa. The adherence club intervention was designed as an adherence-enhancing intervention to enhance the retention in care of patients on ART and their adherence to medication. Although empirical evidence suggests the effective superiority of the adherence club intervention to standard clinic ART care schemes, it is poorly understood exactly how and why it works, and under what health system contexts. To this end, we aimed to develop a refined programme theory explicating how, why, for whom and under what health system contexts the adherence club intervention works (or not). Methods We undertook a realist evaluation study to uncover the programme theory of the adherence club intervention. We elicited an initial programme theory of the adherence club intervention and tested the initial programme theory in three contrastive sites. Using a cross-case analysis approach, we delineated the conceptualisation of the intervention, context, actor and mechanism components of the three contrastive cases to explain the outcomes of the adherence club intervention, guided by retroductive inferencing. Results We found that an intervention that groups clinically stable patients on ART in a convenient space to receive a quick and uninterrupted supply of medication, health talks, counselling, and immediate access to a clinician when required works because patients' self-efficacy improves and they become motivated and nudged to remain in care and adhere to medication. The successful implementation and rollout of the adherence club intervention are contingent on the separation of the adherence club programme from other patients who are HIV-negative. In addition, there should be available convenient space for the adherence club meetings, continuous support of the adherence club facilitators by clinicians and buy-in from the health workers at the health-care facility and the community. Conclusion Understanding what aspects of antiretroviral club intervention works, for what sections of the patient population, and under which community and health systems contexts, could inform guidelines for effective implementation in different contexts and scaling up of the intervention to improve population-level ART adherence.